Uterine Trauma and Intrauterine Fetal Death Caused by Seatbelt Injury - Junsuke Muraoka; Teruo Otsuka; Aya Yamauchi; Kiminari Terao (Hindawi Limited, 2019)
We present a case of uterine trauma and intrauterine fetal death caused by seatbelt injury. A 37-year-old primigravida at gestational week 24 was involved in a single-car accident when traveling as a front-seat passenger and wearing a three-point seatbelt. Fetal heart rate monitoring patterns revealed fetal demise, and computed tomography revealed intraperitoneal bleeding due to damage to the uterine vessels and placental lacerations across the seatbelt-compressed region. Intensive treatment, including transfusion therapy and surgical laparotomy, prevented the loss of her life but not that of the fetus. Seatbelt use can reduce the overall mortality associated with motor vehicle crashes. Pregnant women must be educated on the proper use of restraints while traveling in motor vehicles.